Obtaining Experimental Values of the Uniformity of Seed Distribution by Multivariate Regression Analysis - V. Demchuk , Evgeniy; V. Redreev, Grigoriy; V. Myalo, Vladimir; V. Myalo, Ol'ga; P. Prokopov, Sergey (KnE Life Sciences, 2021)
One of the key factors affecting agricultural productivity is the availability of technical means that include machine and tractor units of agricultural enterprises. The production volume of the plant growing industry depends on high yields that can be achieved by high-quality sowing, which implies the optimal seed placement and sowing depth. Thus, the modernization of existing seeding machines and the creation of new ones that ensure the optimal seed placement is an urgent task. This study aimed to develop a coulter for uniform seed distribution along the furrow length. The object of the study was uniform sowing patterns for grain crops based on the optimal parameters of the proposed working unit of the seeding machine obtained by multivariate regression analysis. A symmetric orthogonal compositional plan of the second order was chosen as a model. The criterion for optimization of the geometric parameters of the developed coulter was the uniformity of seed distribution along the furrow length. The following parameters of the proposed coulter were changed: the cut length of the outer side of the rectilinear profile of the lower edge of the rack varied within 20–80 mm (L), and the approach angle in the horizontal plane (α) and the roll angle in the vertical plane (β) varied within 3–28 deg. The study yielded the regression equation for constructing the response surfaces. The analysis of the response surfaces showed that the optimal parameters for uniform seed distribution along the furrow length can be achieved at the approach angle α=250, the roll angle β=150, and the cut length of the lower edge of the rack L=50 mm. Keywords: Coulter, sowing, grain, quality, distribution uniformity, multivariate experiment